Portfolio de doctorants et postures d’apprenti chercheur - Elsa Chachkine; Fabienne Saboya (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The professionalization of doctoral students is a major challenge in an ever-changing socio-economic context, where strong investment in research and innovation is essential. In France, this requirement for professionalization is framed by a decree on the doctorate (2016 decree), which institutes the portfolio as a tool for doctoral training. This article focuses on the implementation of a portfolio approach in a multidisciplinary doctoral school in human and social sciences at the Cnam in Paris. The approach is designed to enable doctoral students to become aware of and value the competences they have acquired during their doctoral studies, to develop their research posture(s) and to reflect on their new professional identity. The question guiding this research is whether this approach makes it possible to develop a researcher's posture(s), and if so, what posture(s). The results obtained from a qualitative analysis of 25 portfolios (Lejeune, 2019) reveal, on the one hand, two orders of posture, one professional, the other learning, and, on the other hand, an existential dimension interwoven into these two orders. Three professional postures emerge: as transmitter of knowledge, as creator of knowledge and as user of knowledge for expert purposes, which are not mutually exclusive. The learning postures are distinguished by the positioning of reflection in relation to the learning process: from minimal reflexivity to reflective thinking with an advanced critical dimension. This research, which demonstrates the relevance of this portfolio approach for doctoral training, provides a basis for discussion and reflection on the portfolio as a pedagogical tool.